Examining the Impact of Student-Centered Management in Universities on the Effectiveness of Education and Students’ Academic Performance - Farhang Esfahani, Alireza (Assessment and Practice in Educational Sciences, 2026)
This study aimed to examine the impact of student-centered management (SCM) practices in universities on educational effectiveness and students’ academic performance. This research employed a sequential exploratory mixed-method design consisting of a qualitative phase followed by a quantitative validation phase. In the first phase, a systematic literature review was conducted to identify the key dimensions of student-centered management, and data collection continued until theoretical saturation was achieved. The qualitative data were analyzed through thematic analysis using NVivo 14 software, producing six core dimensions: active learning practices, advising and mentorship, participatory decision-making, feedback timeliness, support services integration, and flexible assessment. In the second phase, a structured questionnaire derived from the qualitative findings was administered to 200 university students in Tehran, Iran, selected through simple random sampling. Data were analyzed using SPSS version 26, employing descriptive statistics, Pearson correlations, and multiple regression analyses to assess the predictive relationships between SCM dimensions, educational effectiveness, and academic performance. Inferential results indicated that SCM significantly predicts both educational effectiveness (R² = 0.52, p < .001) and academic performance (R² = 0.45, p < .001). Among SCM dimensions, active learning practices (β = 0.31, p < .001), advising and mentorship (β = 0.21, p = .002), and feedback timeliness (β = 0.17, p = .010) were the strongest predictors of educational effectiveness. Furthermore, educational effectiveness mediated the relationship between SCM and academic performance, suggesting that the management approach enhances achievement primarily through improved teaching quality and engagement. Student-centered management substantially enhances the quality of education and academic performance by fostering active learning, effective mentorship, and timely feedback. Integrating participatory governance and adaptive management strategies can strengthen institutional effectiveness and student outcomes in higher education settings.